Revision of the genus Anomologa Meyrick, 1926, including the description of a new species, and its impact on subfamilies of Gelechiidae (Lepidoptera) - Bidzilya, Oleksiy V.; Karsholt, Ole; Metz, Mark; Rajaei, Hossein (Zootaxa, 2025)
The genus Anomologa Meyrick, 1926 is revised, and its diagnosis is improved. Euryctista Janse, 1963 syn. nov. is considered a junior synonym of Anomologa. Four species, Anomologa dispulsa Meyrick, 1926, A. demens Meyrick, 1926, A. hobohmi (Janse, 1963) comb. nov. and A. terminata sp. nov. are recognized as valid. All Anomologa species are redescribed based on type specimens as well as additional material. Male and female genitalia of Anomologa demens and A. dispulsa, as well as female genitalia of A. hobohmi are described for the first time. Morphological characters of Anomologa indicate its affinity to Apatetris Staudinger, 1879 (type genus of the subfamily Apatetrinae), Chrysoesthia Hübner, 1825, Metanarsia Staudinger, 1871 and other genera of subfamily Apatetrinae, which convinced us to synonymize the family group name: Apatetrinae Le Marchand, 1947 syn. nov. of Anomologinae Meyrick, 1926. Accordingly, Aristoteliinae Le Marchand, 1947 stat. rev. is available for Anomologinae sensu auctorum as the oldest family group name for this taxon. The updated classification of Anomologinae and Aristoteliinae is provided, and the new synonymy is established: Metopios Lucas, 1945 syn. nov. of Catatinagma Rebel, 1903.